IL-6 and IL-8 Are Linked With Myeloid-Derived Suppressor Cell Accumulation and Correlate With Poor Clinical Outcomes in Melanoma Patients - Tobin, Richard P.; Jordan, Kimberly R.; Kapoor, Puja; Spongberg, Eric; Davis, Dana; Vorwald, Victoria M.; Couts, Kasey L.; Gao, Dexiang; Smith, Derek E.; Borgers, Jessica S. W.; Robinson, Steven; Amato, Carol; et al. (Frontiers in Oncology, 2019)
We sought to identify tumor-secreted factors that altered the frequency of MDSCs and correlated with clinical outcomes in advanced melanoma patients. We focused our study on several of the many factors involved in the expansion and mobilization of MDSCs. These were identified by measuring circulating concentrations of 13 cytokines and growth factors in stage IV melanoma patients (n = 55) and healthy controls (n = 22). Based on these results, we hypothesized that IL-6 and IL-8 produced by melanoma tumor cells participate in the expansion and recruitment of MDSCs and together would be predictive of overall survival in melanoma patients. We then compared the expression of IL-6 and IL-8 in melanoma tumors to the corresponding plasma concentrations and the frequency of circulating MDSCs. These measures were correlated with clinical outcomes. Patients with high plasma concentrations of either IL-6 (40%) or IL-8 (63%), or both (35%) had worse median overall survival compared to patients with low concentrations. Patients with low peripheral concentrations and low tumoral expression of IL-6 and IL-8 showed decreased frequencies of circulating MDSCs, and patients with low frequencies of MDSCs had better overall survival. We have previously shown that IL-6 is capable of expanding MDSCs, and here we show that MDSCs are chemoattracted to IL-8. Multivariate analysis demonstrated an increased risk of death for subjects with both high IL-6 and IL-8 (HR 3.059) and high MDSCs (HR 4.265). Together these results indicate an important role for IL-6 and IL-8 in melanoma patients in which IL-6 potentially expands peripheral MDSCs and IL-8 recruits these highly immunosuppressive cells to the tumor microenvironment. This study provides further support for identifying potential therapeutics targeting IL-6, IL-8 and MDSCs to improve melanoma treatments.